An approximate solution of fractional cable equation by homotopy analysis method - Inc, Mustafa; Cavlak, Ebru; Bayram, Mustafa (SPRINGEROPEN, 2014)
In this article, the homotopy analysis method (HAM) is applied to solve the fractional cable equation by the Riemann-Liouville fractional partial derivative. This method includes an auxiliary parameter h which provides a convenient way of adjusting and controlling the convergence region of the series solution. In this study, approximate solutions of the fractional cable equation are obtained by HAM. We also give a convergence theorem for this equation. A suitable value for the auxiliary parameter h is determined and results obtained are presented by tables and figures.
Keywords: cable equation; fractional differential equations; fractional cable equation; homotopy analysis method; Mathematics